RESISTANCE TO STEREOTYPES AND DISCRIMINATION IN ZOOTOPIA (2016) - Yahya, Wirda Humaira; Hikmat, Mahi M (Universitas Negeri Surabaya, 2024)
Zootopia is an animated film released in 2016 by Walt Disney Animation Studios. This movie not only offers entertainment for various audiences, but also conveys a deep social message about resistance to stereotypes and discrimination. This study uses narrative theory. Todorov (1971) put forward the concept of